Selected models for the description of the kinematics of changes of height differences between points in a geodesic network under the influence of mining = Wybrane modele opisu kinematyki sieci geodezyjnej wysokościowej pod wpływem eksploatacji górniczej - Mrówczyńska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article attempts to describe the progress of deformation of the surface of the Legnica-Głogów Copper Mining Area in the years 1967-2008. The state of deformation has been described with kinematical models of the displacement of points representing the area under research.
Keywords: teren eksploatacji górniczej; deformacja powierzchni; Legnicko-Głogowski Okręg Miedziowy; sieci geodezyjne; sieci neuronowe; model przemieszczeń pionowych; deformation of surface; Legnica-Głogów Copper Mining Area; reference system; model of vertical displacements; neutral networks